Comparison of Effect between Inhalative Anesthetics with Isoflurane and Sevoflurane on Oxygen Saturation - Setiawan, Prabuwinoto; Sudjito, M.H.; Probandari, Ari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
ABSTRACT Â Background: Inhalative anesthesia with isoflurane and sevoflurane are known to lower the oxygen saturation in patients. Both of these agents reduce the ventilation response to hypoxia. This study aimed to compare the effect of giving inhaled anesthetics isoflurane and sevoflurane to changes in oxygen saturation. Methods: This study was an observational analytic study with cross-sectional approach. The study was conducted at the Central Installation of Surgery dr. Moewardi Hospital. Samples were taken by consecutive sampling. There were two groups in this study, the group that received isoflurane anesthesia and sevoflurane anesthesia. Each group was observed for the changes in oxygen saturation during the operation using the bed side monitor. The data which have been collected then be analyzed using the Mann Whitney test and Pearson correlation test. Results: These results revealed that in both groups, isoflurane and sevoflurane, there was a decrease in oxygen saturation in the induction phase (sevoflurane = 97.42 Â± 0.90; isoflurane = 97.00 Â± 0.75; p = 0.113). However, after the induction phase the oxygen saturation among the patients of the isoflurane group was more fluctuating than the ones of the sevoflurane group (p intubation = 0.001; p incision 5â = 0.117; p incision 10â = 0.001; p incision 15â = 0.048). The further analysis showed no statistically significant difference in oxygen saturation between the isoflurane and the sevoflurane groups (p = 0.113). Conclusions: There are no significant differences in changes of oxygen saturation between the isoflurane and sevoflurane anesthesia on the induction phase, 5 minutes after incision and 15 minutes after incision. Anesthesia with sevoflurane in oxygen saturation is more stable compared with isoflurane anesthesia on intubation phase up to 15 minutes after incision. Keywords: inhalation anesthesia, sevoflurane, isoflurane, hemodynamic, oxygen saturation